Organizational Principles of Development of Golf in Ukraine. An Overview of Strategic Planning - Oksana Shynkaruk; Myroslav Dutchak; Vitaly Usychenko; Marina Lavrenchuk; Anastasia Ponomarenko; Maksym Yarmolenko; Yuriy Michuda (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
The article analyses the modern trends of world golf. The experience of national golf federations of the world's leading countries, interviews with golf experts assisted (29 participants in the survey: including 8 representa- tives of the National Olympic Committee (NOC), 10 members of the Board of the Ukrainian Golf Federation, 6 golf judges, 5 coaches and golf instructors) to identify the specific features of golf development and popular- ization trends. The modern causes affecting further development of golf in Ukraine are investigated: the defi- ciencies of the legislative provision of sports development and the promotion of the activities of subjects of the national golf system; low level of motivation of different groups of population for golf to practice in the country; lack of golf courses at children's and youth sports schools; the backlog of the material and technical base of golf development from the level of most countries of the world; mismatch with the modern requirements of scien- tific and methodological support for the development of golf and staffing, and others. The strategic directions, goals and objectives for the development of golf in Ukraine for the period up 2030 are resulting from this study. The strategy of golf development in Ukraine will allow dignified representation of the state in the world sports community, popularize golf as a leisure activity in the system of a healthy lifestyle of citizens and promote the consolidation of the nation.